Early cessation and non-response are important and possibly related problems in growth hormone therapy: An OZGROW analysis. (August 2016) - Hughes, Ian P.; Choong, Catherine; Rath, Shoshana; Atkinson, Helen; Cotterill, Andrew; Cutfield, Wayne; Hofman, Paul; Harris, Mark
Abstract: Objective: To investigate growth hormone (GH) treatment and treatment cessation with respect to efficacy and efficiency. To identify factors that best classify or predict cessation type: completed treatment (CT), early cessation (EC), or non-response (NR). Design: Observational study (1990–2013) of the Australian GH Program comparing CT, EC, and NR groups with respect to demographic, clinical, and response criteria. All patients treated for GH deficiency (GHD; 909), short stature and slow growth (SSSG; 2144), and Turner Syndrome (TS; 626) were included. Information was retrieved from the OZGROW database. Results: 51.9% of patients were EC, 40.7% CT and 7.4% NR.Median treatment durations for NR patients were often longer than patients who completed treatment. EC and NR groups were both associated with poor growth response with males overrepresented.Socioeconomic status differentiated NR (higher) and EC (lower) groups. Conclusions: EC was observed at very high rates and appears, generally, to be a little-recognised but frequent problem in GH therapy.EC and delayed recognition of NR may be interrelated being differentiated by the decision to cease or continue treatment following poor response.Poor treatment compliance is likely a major causal factor in EC.Strategies to address poor response and compliance have been developed, however, given the scale of these problems, it may be that long acting GH formulations or individualized treatment need consideration. Highlights: 51.9% of GH patients ceased treatment earlier than they were required to. Treatment duration for non-responsive patients was often longer than for patients who completed their treatment. Early ceasing and non-responsive groups were both associated with poor growth response. Until recently males were also overrepresented in both groups. Socioeconomic status differentiated non-responsive (higher) and early ceasing (lower) groups. Early cessation and delayed recognition of non-response may be interrelated being differentiated by the decision to cease or continue treatment following poor response. Poor treatment compliance and persistence is likely a major causal factor in early cessation.